ALL ASSUMPTIONS ARE PRESUMABLE: THE EIGHTH PLAGUE. ESSAY - HARUTYUNYAN, EDUARD (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
Much has changed since the waters of the earth parted from the land, the light from the darkness, the sky from the earth, each with its own eidos. Step by step modern civilization is forming a strange mixture of one-dimensioned and uniformed world, where all the people seem to typify the same eidos and are interchangeable identities without individualities. They are everybody and at the same time nobody. They are a mixture of formless ones, who don’t adapt to each other, but obediently accept their identity, and don’t have their own reason for living.
Keywords: eidos, Hermes Trismegistus, Plato, Buddha, esotericism, unpreconditioned opportunities, one-dimensionality, identity, Third Man